2018
DOI: 10.1038/s41467-018-05910-1
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB inhibition rescues cardiac function by remodeling calcium genes in a Duchenne muscular dystrophy model

Abstract: Duchenne muscular dystrophy (DMD) is a neuromuscular disorder causing progressive muscle degeneration. Although cardiomyopathy is a leading mortality cause in DMD patients, the mechanisms underlying heart failure are not well understood. Previously, we showed that NF-κB exacerbates DMD skeletal muscle pathology by promoting inflammation and impairing new muscle growth. Here, we show that NF-κB is activated in murine dystrophic (mdx) hearts, and that cardiomyocyte ablation of NF-κB rescues cardiac function. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 70 publications
2
29
0
Order By: Relevance
“…Many molecules have been tested to target this master regulator of inflammation ( Table 3 ). In mdx myotubes or mice, several studies were performed with NF-κB inhibitors, such as NK-κB Essential MOdulator (NEMO)-Binding Domain (NBD), the antioxidant pyrrolidine dithiocarbamate (PDTC), the inhibitor of lipid peroxidation IRFI-042, and the free radical scavengers, N-acetylcysteine (NAC) and (ALA)/L-carnitine (L-Car) [ 31 , 37 , 38 , 39 , 40 , 41 , 42 ]. Unfortunately, NBD induced renal toxicity in mdx mice despite encouraging results showing decreased necrosis and increased regeneration in the diaphragm and hind limb muscles [ 37 , 43 , 44 ].…”
Section: Activation Of the Cellular Pathways In Skeletal Muscle Cementioning
confidence: 99%
“…Many molecules have been tested to target this master regulator of inflammation ( Table 3 ). In mdx myotubes or mice, several studies were performed with NF-κB inhibitors, such as NK-κB Essential MOdulator (NEMO)-Binding Domain (NBD), the antioxidant pyrrolidine dithiocarbamate (PDTC), the inhibitor of lipid peroxidation IRFI-042, and the free radical scavengers, N-acetylcysteine (NAC) and (ALA)/L-carnitine (L-Car) [ 31 , 37 , 38 , 39 , 40 , 41 , 42 ]. Unfortunately, NBD induced renal toxicity in mdx mice despite encouraging results showing decreased necrosis and increased regeneration in the diaphragm and hind limb muscles [ 37 , 43 , 44 ].…”
Section: Activation Of the Cellular Pathways In Skeletal Muscle Cementioning
confidence: 99%
“…Further studies in animal models showed misregulation of other ion channels such as voltage-gated Nav1.5 and L-type calcium channel (LTCC) hyperactivation (Koenig et al, 2011), as well as upregulation of inflammation-related induced nitric oxide synthase (iNOS) (Fauconnier et al, 2010;Peterson et al, 2018). Such observations remain to be validated in human DMD.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Regulatory T cells have been shown to block and/or ameliorate dystrophic symptoms in mouse and canine DMD models. 7,17,[19][20][21][22][23][24][25][26] The nuclear pore functions as a key regulator of intracellular molecules such as proteins, RNA molecules, and ions. 27,28 The nuclear pore consists of various regulatory proteins called nucleoporins that together form the nuclear pore complex (NPC).…”
Section: Introductionmentioning
confidence: 99%